A simplified approach to estimate the sustainable lifestyle level for retirement planning. Issue 3 (2nd July 2020) - Roux, Elze-Mari; de Villiers, Johann
ABSTRACT: In this article we offer a simplified version of the alternative retirement planning model we originally proposed (De Villiers & Roux, 2019 ). Our method focuses on determining the sustainable lifestyle level (SLL) that an individual can currently afford while still saving enough towards retirement to sustain this lifestyle level up to retirement and beyond. The model is simplified by assuming that the real rate of return on retirement savings before retirement will be the same as the withdrawal rate of income from the accumulated savings during retirement. This method yields a much simpler SLL relationship in that it is more generally applicable albeit possibly less accurate. This approach should improve communication of the extent of the retirement savings challenge, possibly leading to better savings outcomes.